Muti-indicator integrated assessment of coastal erosion vulnerablity in the Abandoned Yellow River Delta using geospatial approaches - Zhi Zhang; Zhi Zhang; Kai Zhou; Kai Zhou; Peng Chen (Frontiers in Marine Science)
Coastal erosion is the leading marine hazard in the Abandoned Yellow River Delta, and coastal erosion vulnerability assessment is essential for disaster mitigation and risk reduction. To comprehensively reflect the erosion status of the coast of the Abandoned Yellow River Delta, a ICVI index that integrates the composition of coastal dynamics(Mean tidal range, Mean significant wave height, Storm surge height), coastal morphology(Seawall Elevation, Rate of coastline change, Rate of tidal flat erosion, Coastal slope, Tidal flat width), and socioeconomic indicators(Population density, Land use, Roads, Artificial protection) was constructed. After that, the coastal erosion vulnerability assessment of the Abandoned Yellow River Delta was carried out, and the physical and socioeconomic vulnerability was calculated and then combined to create an integrated coastal vulnerability index (ICVI). The driving factors and the interactions between these factors of coastal erosion vulnerability were analyzed by using a geodetector method. The results showed that the proportions of the very high, high, medium, low, and very low vulnerability of the whole coast were 13.62%, 19.31%, 18.29%, 27.28%, and 21.5%, respectively. The very high vulnerable areas were mainly distributed in Xiangshui, Binhai, and Sheyang. The coastal erosion vulnerability generally showed a distribution pattern high in the north and low in the south. The spatial differentiation of coastal erosion vulnerability results from the synergistic effect of multiple factors such as coastal dynamics, coastal morphology, and socioeconomic indicators, among which Rate of tidal flat erosion is the dominant factor in the spatial differentiation of coastal erosion vulnerability. The interaction results showed that coastal erosion protection requires the synergistic effect of multiple measures, especially coastline protection and tidal flats erosion protection, which are the most beneficial for coastal erosion protection. The vulnerability maps developed in this study can provide reliable spatial information for the relevant authorities to formulate better erosion risk mitigation policies.